Narrative strategies in the origin of journalism: An analysis of the first Spanish-language gazettes - Díaz Noci, Javier (Anàlisi, 2017)
The topic of our study is journalism as a narrative genre. Before becoming periodical, newssheets adopted many forms at the end of the sixteenth and throughout the seventeenth centuries, which we aim to typologize before conducting a corpus-based analysis (Biber, 2009, 2012), in which pre-determined categories will be applied in search of patterns. In order to prove the validity and productivity of this approach in an exploratory manner, we have applied those methods to a reduced corpus of some of the first gazettetype printed newssheets in the Spanish language, so as to longitudinally extend this strategy in further research to many other corpora of miscellaneous newssheets. This first tentative sample is composed of four newssheets published from 1597 to 1621, our goal being to trace the patterns and continuities of a narratological model for the early days of Spanish journalism. In our opinion, and following an Italian style detailed by Panfilo Persico in Il Segretario (Venice, 1620), narrative newswriting strategies, at least in the Mediterranean area, were most especially consolidated during the Thirty Years War (1618-1648), and were even present in Spanish gazettes in one of the most flourishing periods of activity, the decade of 1683, because of the Turkish Wars (Díaz Noci, 2008).